"She Gave Me the Confidence to Open Up": Bridging Communication by Promotoras in a Childhood Obesity Intervention for Latino Families. (October 2017) - Falbe, Jennifer; Friedman, Lily E.; Sokal-Gutierrez, Karen; Thompson, Hannah R.; Tantoco, Nicole K.; Madsen, Kristine A.
Childhood obesity is a public health threat that disproportionally affects Latino youth in the United States. Active and Healthy Families (AHF) is a culturally tailored, family-based program for addressing obesity disparities in a predominantly immigrant Latino population. AHF was the first primary care, culturally tailored intervention for Latino children to significantly reduce BMI in a randomized controlled trial. The 10-week AHF intervention reduced BMI (kg/m 2 ) among overweight or obese children by 0.5, compared with an increase of 0.3 in the control group, yielding a −0.8 difference ( p < .01). A unique aspect of the program is its provider team: a physician, dietitian, and promotora . Because early feedback from families highlighted the importance of promotoras specifically, we sought to understand the unique mechanisms of promotora effectiveness in AHF. We conducted in-depth, semistructured interviews with the AHF providers ( n = 5) and parent participants ( n = 23) by phone between November 2012 and May 2013. In a grounded theory analysis, three main categories encompassing five themes emerged: (a) bridging communication by promotoras; (b) promotoras' personal qualities, including themes of kindness and caring and shared experiences with patients; and (c) impactful task performance, including themes of motivation, positive environment, and self-efficacy. Together, the themes serve as the basis of a conceptual model illustrating the process through which promotoras may enhance the impact of team-based obesity programs for the Latino community. Because this study identifies the specific ways through which promotoras can bridge cultural, linguistic, and other divides, it may inform development and dissemination of evidence-based approaches for obesity prevention in the Latino community.